The role of LGR4 in bone metabolism and tumor bone metastasis - Huang, Jiawang; Jin, Yucheng; Yi, Zhigang (Frontiers in Endocrinology, 2025)
The Leucine-rich repeat-containing G protein-coupled receptor 4 (LGR4) is a member of the G protein-coupled receptor family and plays an important role in bone metabolism and tumor bone metastasis. LGR4 affects bone metabolism by regulating the differentiation and activity of osteoblasts and osteoclasts, and is involved in the balance between bone resorption and bone formation. Deficiency of LGR4 leads to osteoporosis, whereas the up-regulation of LGR4 may help to alleviate the development of traumatic osteoarthritis. Furthermore, in breast cancer and multiple myeloma, LGR4 promotes tumor cell metastasis to bone tissue by activating related signaling pathways. Therefore, LGR4 may be a potential target for the treatment of bone metabolic diseases and tumor bone metastasis.